Expression of Evc2 in craniofacial tissues and craniofacial bone defects in Evc2 knockout mouse. (August 2016) - Badri, Mohammed K.; Zhang, Honghao; Ohyama, Yoshio; Venkitapathi, Sundharamani; Alamoudi, Ahmed; Kamiya, Nobuhiro; Takeda, Haruko; Ray, Manas; Scott, Greg; Tsuji, Takehito; Kunieda, Tetsuo; Mishina, Yuji; et al.
Highlights: Evc2 knockout mouse was generated by introducing a stop codon followed by IRES-LacZ. This IRES-LacZ cassette allows us to identify the Evc2-expressing cells. Evc2-expressing cells were mainly chondrocytes in the anterior viscerocranium. Endogenous EVC2 protein was observed in these corresponding cells. Evc2 deficiency showed abnormal craniofacial bones in the anterior viscerocranium. Abstract: Objective: Our objectives were to determine the expression of EVC2 in craniofacial tissues and investigate the effect of Evc2 deficiency on craniofacial bones using Evc2 knockout (KO) mouse model. Design: Evc2 KO mice were generated by introducing a premature stop codon followed by the Internal Ribosomal Entry Site fused to β-galactosidase (LacZ). Samples from wild-type (WT), heterozygous (Het) and homozygous Evc2 KO mice were prepared. LacZ staining and immunohistochemistry (IHC) with anti-β-galactosidase, anti-EVC2 and anti-SOX9 antibodies were performed. The craniofacial bones were stained with alcian blue and alizarin red. Results: The LacZ activity in KO was mainly observed in the anterior parts of viscerocranium. The Evc2 -expressing cells were identified in many cartilageous regions by IHC with anti-β-galactosidase antibody in KO and Het embryos. The endogenous EVC2 protein was observed in these areas in WT embryos. Double labeling with anti-SOX9 antibody showed that these cells were mainly chondrocytes. At adult stages, the expression of EVC2 was found in chondrocytes of nasal bones and spheno-occipital synchondrosis, and osteocytes and endothelial-like cells of the premaxilla and mandible. The skeletal double staining demonstrated that craniofacial bones, where the expression of EVC2 was observed, in KO had the morphological defects as compared to WT. Conclusion: To our knowledge, our study was the first to identify the types of Evc2 -expressing cells in craniofacial tissues. Consistent with the expression pattern, abnormal craniofacial bone morphology was found in the Evc2 KO mice, suggesting that EVC2 may be important during craniofacial growth and development.